1997
DOI: 10.1074/jbc.272.8.5354
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetic Mechanism of Serpin-Proteinase Complex Formation

Abstract: Serine proteinase inhibitors (serpins) form enzymatically inactive, 1:1 complexes (denoted E*I*) with their target proteinases that release free enzyme and cleaved inhibitor only very slowly. The mechanism of E*I* formation is incompletely understood and continues to be a source of controversy. Kinetic evidence exists that formation of E*I* proceeds via a Michaelis complex (E⅐I) and so involves at least two steps. In this paper, we determine the rate of E*I* formation from ␣-chymotrypsin and ␣ 1 -antichymotryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 50 publications
3
31
0
Order By: Relevance
“…In our own work, both current and previous (5,22,23), on the ACT/Chtr interaction, we have shown that large fluorescent changes, from probes placed at the P7, P13, and P1Ј positions in ACT precede E*I* formation. Similar conclusions from time-resolved studies have been reported for the interactions of antithrombin (AT) and thrombin (14) and antitrypsin and elastase (45).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our own work, both current and previous (5,22,23), on the ACT/Chtr interaction, we have shown that large fluorescent changes, from probes placed at the P7, P13, and P1Ј positions in ACT precede E*I* formation. Similar conclusions from time-resolved studies have been reported for the interactions of antithrombin (AT) and thrombin (14) and antitrypsin and elastase (45).…”
Section: Discussionmentioning
confidence: 99%
“…Construction, Expression, and Purification of rACTs-S359C-rACT was constructed using sequence overlap expression polymerase chain reaction and the ACT expression vector described previously (20,22). The internal primers coding for the Ser 3 Cys mutation are as follows: 5Ј-CCCTCCTTTGTGCATTAGTGGAGACA-3Ј and 5Ј-GCACAAAGGA-GGGTGATTTTGAC-3Ј (the mutation sites are in boldface).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations